Managing public debt in Europe: an introductory guide - Theodoropoulou, Sotiria (Brussels, 2018)
"This new introductory guide, ‘Managing public debt in Europe, reviews the debate and empirical evidence on the problems that high public debt may cause and the policy options for reducing it. To do so, it starts from the basics regarding the determinants of the evolution of public debt over time, explains under what conditions high public debt can lead to a crisis and reviews the theory and evidence on whether high public debt is detrimental for growth."